Exploring Job Satisfaction Behavior as an Antecedent and Moderating Variable of Work Engagement In the Public Sector - Fitriani, Arbania; Wihana Kirana Jaya; Sumaryono, Sumaryono; Rosari, Reni (International Journal of Economics (IJEC), 2024)
This study investigates the role of multifaceted job satisfaction as an antecedent variable and moderating factor influencing work engagement in the public sector. Drawing upon Bakker and Demerouti's (2007) model, the research adapts Spector's (1997) job satisfaction measurement constructs and tests them on a sample of 1484 employees. Employing a mixed-methods approach with a cross-sectional design, the study focuses on identifying key drivers of work engagement in the aftermath of the COVID-19 pandemic. All dimensions are constructed based on qualitative exploration through Focus Group Discussions (FGD) involving 122 respondents, and item formulation is guided by the mapping of dimensions using In-Vivo software. The study employs bootstrapping techniques, revealing a Structural Equation Modeling (SEM) result with a Standardized Root Mean Residual (SRMR) value of 0.054 (<0.08), indicating a perfect fit for the model. All path coefficient indices exhibit a P-Value of 0.000 (<0.05), signifying the acceptance of all proposed relationships in the study. The findings contribute to understanding the intricate interplay between job satisfaction, personal factors, organizational factors, and work engagement, providing valuable insights for practitioners and policymakers in the public sector post-COVID-19.